Integrating Local Wisdom In Transformative Islamic Education: A Sustainable Model For Character Development At Madrasah Aliyah - Taufikin Taufikin (Program Pascasarjana IIQ Jakarta, 2025)
Islamic education in Indonesia faces the challenge of integrating rich local values with more holistic educational goals. This study explores local wisdom's application in transformative Islamic education, focusing on student character development at MAN 1 Kudus and MAN Demak. Using a qualitative approach with a case study design, data were collected through in-depth interviewed to 18 informants, participatory observation and document analysis. The results showed that integrating local values such as unggah-ungguh, guyub, srawung, and nrimo ing pandum has successfully strengthened students' character in social responsibility, tolerance, and spiritual resilience. However, the main challenges in implementation are the diversity of local values in Indonesia and educators' limited understanding of the importance of local wisdom integration. The findings suggest further training for educators and closer collaboration between madrasahs, families and communities. This research contributes to developing local wisdom-based Islamic education models and opens opportunities for further studies on applying similar models in different cultural contexts.